CLINICAL OUTCOMES OF TRANSORAL ENDOSCOPIC THYROIDECTOMY VESTIBULAR APPROACH FOR EARLY-STAGE PAPILLARY THYROID CARCINOMA AT HANOI ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Transoral endoscopic thyroidectomy vestibular approach (TOETVA) is an advanced technique providing superior cosmetic outcomes by leaving completely scarless skin.Objective: To evaluate the early surgical outcomes of TOETVA for papillary thyroid cancer at Hanoi Oncology Hospital. Patients and Methods: This is a descriptive retrospective/prospective series of surgical cases on 195 patients with early-stage papillary thyroid cancer cT1N0M0, who underwent TOETVA from September 2022 to March 2026 at Hanoi Oncology Hospital. Results: The mean age of the patients was 40.21 ± 8.56 years, with females accounting for 97.4%. The primary reason for admission was incidental thyroid nodules detected during routine check-ups (94.4%). The mean tumor size on ultrasound was 8.21 ± 2.5 mm, with microcarcinomas (< 10 mm) comprising 84%. Regarding surgical procedures, 92.3% of patients underwent lobectomy + isthmectomy + central neck dissection (CND), and 7.7% underwent total thyroidectomy + CND. No cases required conversion to open surgery. The mean operative time was 95 ± 7 minutes. The mean number of harvested lymph nodes was 4.98 ± 2.12, and the occult central lymph node metastasis rate was 14.9%. The most common complication was subcutaneous ecchymosis (10.8%), followed by transient hoarseness (4.1%), seroma (3.07%), and transient hypoparathyroidism (1%). No permanent complications or mental nerve injuries were recorded. The mean hospital stay was 3.75 ± 0.87 days. Conclusion: TOETVA is a feasible and safe approach for the treatment of early-stage papillary thyroid carcinoma, providing favorable early surgical outcomes and the cosmetic advantage of avoiding visible cervical scars.
Keywords: Papillary thyroid cancer, TOETVA, Transoral endoscopic thyroidectomy, Central lymph node dissection.